Error Analysis and Method of Translation in Face Care Product Labels - Iin Indrayanti; Adi Kuntoro; Syaefani Arif Romadhon (East Asian Journal of Multidisciplinary Research, 2023)
The current study was aimed to conduct additional analysis and findings further about any deviations or errors from the translation results, as well as the dominant method of translation used by the translator in three packaging labels of face care products that are widely flow in the Indonesian community. Data were collected from three local brands' packaging labels of popular face care products among Indonesian women. Data analysis consisted of words, phrases, and sentences all of which were bilingually translated from Indonesian into English and printed in the Direction for Use or How to Use the product. The research discovered that the majority of translation inaccuracies from the three packaging labels of the products were Mistranslation, Terminology, Omission, Addition, and Word From error.